2023
DOI: 10.1002/jbm4.10817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Incretin Therapy on Skeletal Health in Type 2 Diabetes—A Systematic Review

Rikke Viggers,
Nicklas Højgaard‐hessellund Rasmussen,
Peter Vestergaard

Abstract: Diabetes poses a significant risk to bone health, with Type 1 diabetes (T1D) having a more detrimental impact than Type 2 diabetes (T2D). The group of hormones known as incretins, which includes gastric inhibitory peptide (GIP) and glucagon‐like peptide 1 (GLP‐1), play a role in regulating bowel function and insulin secretion during feeding. GLP‐1 receptor agonists (GLP‐1 RAs) are emerging as the primary treatment choice in T2D, particularly when atherosclerotic cardiovascular disease is present. Dipeptidyl pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…In type 2 diabetes, use of metformin [97,98], dipeptidyl peptidase-4 (DPP-4) inhibitors [99] and glucagon-like peptide-1 receptor agonists (GLP1-RAs) [100] appears to be neutral/beneficial with regard to BMD and fracture risk. Incretin therapies (DPP-4 inhibitors and GLP1-RAs) may directly promote bone formation and inhibit bone resorption [100].…”
Section: Bone Treatments Diabetes Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In type 2 diabetes, use of metformin [97,98], dipeptidyl peptidase-4 (DPP-4) inhibitors [99] and glucagon-like peptide-1 receptor agonists (GLP1-RAs) [100] appears to be neutral/beneficial with regard to BMD and fracture risk. Incretin therapies (DPP-4 inhibitors and GLP1-RAs) may directly promote bone formation and inhibit bone resorption [100].…”
Section: Bone Treatments Diabetes Treatmentsmentioning
confidence: 99%
“…In type 2 diabetes, use of metformin [97,98], dipeptidyl peptidase-4 (DPP-4) inhibitors [99] and glucagon-like peptide-1 receptor agonists (GLP1-RAs) [100] appears to be neutral/beneficial with regard to BMD and fracture risk. Incretin therapies (DPP-4 inhibitors and GLP1-RAs) may directly promote bone formation and inhibit bone resorption [100]. Treatment with liraglutide prevented bone loss and increased bone formation marker levels following low energy diet-induced weight loss in women with obesity and without diabetes [101].…”
Section: Bone Treatments Diabetes Treatmentsmentioning
confidence: 99%
“…The promising target Dipeptidyl peptidase 4 (DPP4) was selected as the macromolecular receptor and fetched from the Protein Data Bank with PDB ID "2ONC" [31]. DPP4 has been chosen for its broad relevance in the field of in silico drug design research, due to its pivotal role in the degradation of incretin hormones, which are known to stimulate the secretion of insulin [15]. The protein was modified with MGL-Auto-DockTools v.1.5.6 and energy minimized using SWISS-PDB viewer v4.…”
Section: Target Protein Preparationmentioning
confidence: 99%
“…The Dipeptidyl peptidase 4 (DPP4) enzyme is a key player involved in the regulation of glucose homeostasis [14] and plays a critical role in degrading incretin hormones that stimulate insulin secretion. Inhibiting DPP4 can enhance incretin activity, leading to improved glycemic control in individuals with diabetes [15]. Several SBDD studies have used this enzyme as the target protein to propose some bioactive phytochemicals as antidiabetic drug candidates from various angiosperms, such as Pueraria tuberosa, Moringa oleifera, Ocimum tenuiflorum and Amberboa ramosa [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in vitro and on animals have shown that GLP-1RAs, and in particular liraglutide and exenatide, appear to have a positive effect on bone by stimulating new bone formation and reducing bone resorption. In fact, many of these studies have shown that treatment with GLP-1RAs reduces carboxy-terminal telopeptide (CTX) levels and tends to increase those of alkaline phosphatase (ALP) and amino-terminal propeptide of type I pro-collagen (PINP) [ 8 , 9 ]. Furthermore, some studies conducted on ovariectomized mice or rats have reported that the administration of GLP-1RAs increases BMD and appears to have a protective effect on bone microstructure [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%